Exploring indigenous occupation: reflections from a fieldwork experience in an Ati Community in Southern Cebu - Bulan, Paolo Miguel; Pestaño, Nikki; Sy, Michael (The Journal of Practice Teaching and Learning, 2023)
Framing indigenous doings from an occupational perspective warrant the consideration of pluralistic perspectives. This case study explored the indigenous occupations of an Ati tribe community in Southern Cebu through a fieldwork activity in an occupational therapy undergraduate program. Data were collected through individual interviews, field notes, and journaling and were analysed using constant comparison. Findings revealed three emergent themes: (1) Formations and transformations of indigenous occupations, (2) Valued yet health-compromising indigenous occupations, and (3) Balancing indigenous culture and daily survival. The nuances of the indigenous occupational engagement of the Ati people characterize their doings as gender fluid, promotive, risky, and underpinned by a constant struggle between preserving their culture and survival. Implications of this study include the need for occupational therapy students and practitioners to continue working towards co-creating partnerships with indigenous peoples for learning, praxis, and scholarship. These partnerships can be cultivated by integrating occupational science theorizations in the curriculum, employing decolonizing pedagogies, and encouraging interprofessional learning and working.